2011
DOI: 10.1186/1758-5996-3-1
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive method to estimate anaerobic threshold in individuals with type 2 diabetes

Abstract: BackgroundWhile several studies have identified the anaerobic threshold (AT) through the responses of blood lactate, ventilation and blood glucose others have suggested the response of the heart rate variability (HRV) as a method to identify the AT in young healthy individuals. However, the validity of HRV in estimating the lactate threshold (LT) and ventilatory threshold (VT) for individuals with type 2 diabetes (T2D) has not been investigated yet.AimTo analyze the possibility of identifying the heart rate va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
106
1
8

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(125 citation statements)
references
References 38 publications
(56 reference statements)
10
106
1
8
Order By: Relevance
“…An increasing amount of evidence shows that the HRVT point coincides with the ventilatory and lactate threshold 4,11,12,13 , which are considered simple and practical measures for estimating the aerobic/anaerobic transition. Therefore, our results suggest that, beyond being a valid indicator of parasympathetic withdrawal, HRVT is a reproducible measure in a submaximal exercise test.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An increasing amount of evidence shows that the HRVT point coincides with the ventilatory and lactate threshold 4,11,12,13 , which are considered simple and practical measures for estimating the aerobic/anaerobic transition. Therefore, our results suggest that, beyond being a valid indicator of parasympathetic withdrawal, HRVT is a reproducible measure in a submaximal exercise test.…”
Section: Discussionmentioning
confidence: 99%
“…The point where the values in these two parasympathetic indices are stabilized is called the heart rate variability threshold (HRVT) and is considered an indicator of parasympathetic deactivation during an incremental exercise test 6,7,11 . Recent publications demonstrated that HRVT coincided with the first ventilatory threshold and lactate threshold, suggesting that HRVT might be a practical and attractive alternative to identify adequate workload for exercise prescription 4,12,13 . Conversely, analysis of vagal activity immediately post-exercise has been considered a complementary alternative for monitoring training status and control of internal load 14,15,16 .…”
Section: Introductionmentioning
confidence: 99%
“…16 The peak treadmill velocity (PTV) is defined as the final velocity reached and maintained for one minute for a maximum incremental test, which is associated with VO 2 max 17 and significantly correlated with the Maximal Aerobic Speed (vVO 2 max) (r = 0.90). 18 Determination of Lactate Threshold (LT) was conducted through the HRV and following the criteria used by Sales et al 19 Briefly, during low to moderate exercise intensity the heart rate increase is mainly controlled by the parasympathetic nervous system (PNS) withdrawal, but at higher intensities there is a reduction in HRR, heart rate reserve.…”
Section: Experimental Design Peak Treadmill Velocity (Ptv) Determinationmentioning
confidence: 99%
“…The maximal oxygen consumption (VO 2max ) and anaerobic threshold (AT) are parameters that have been widely considered as hallmarks of aerobic fitness for athletes (Svedahl and MacIntosh, 2003), physically active individuals (Simões et al, 2003) and, to a minor scale, for special populations (Belli et al, 2007;Motta et al, 2010;Sales et al, 2011). AT can be used in specific aerobic evaluations and is considered a gold standard parameter for exercise prescription, including cardiovascular risks groups (Belli et al, 2007;Farsidfar et al, 2008).…”
Section: Introductionmentioning
confidence: 99%